Diagnostic performance and clinical impact of photon-counting detector computed tomography in coronary artery disease - Roosha Parikh; Doosup Shin; Ziad A. Ali; Omar K. Khalique (Current Opinion in Cardiology, 2026)
Purpose of review Photon-counting detector computed tomography (PCD-CT) is an emerging technology that addresses key limitations of conventional coronary CT angiography, including calcium blooming, stent-related artifacts, and limited spatial resolution. This review summarizes recent evidence regarding the diagnostic performance and clinical impact of PCD-CT in the evaluation of coronary artery disease (CAD) and discusses its potential role in contemporary cardiovascular imaging. Recent findings Recent studies demonstrate that PCD-CT provides superior spatial resolution, improved contrast-to-noise ratio, and reduced blooming artifacts compared with conventional energy-integrating detector CT. Clinical investigations have shown improved diagnostic accuracy for detecting obstructive CAD, particularly in patients with heavy coronary calcification, older patients and coronary stents. Large observational studies report higher specificity, improved positive predictive value, fewer indeterminate examinations, reduced invasive coronary angiography referrals, and greater revascularization yield. Emerging applications include advanced plaque characterization, extracellular volume quantification, and ultra-low-dose radiation and contrast imaging. Summary Current evidence suggests that PCD-CT represents a transformative advancement in noninvasive coronary imaging. Beyond improving diagnostic accuracy, PCD-CT may enhance clinical decision-making, reduce unnecessary downstream testing, and expand the role of CT in comprehensive cardiovascular assessment. Future multicenter outcome studies and standardized imaging protocols will be essential to establish its long-term clinical and economic value.